Isolation and characterization of halotolerant plant growth promoting rhizobacteria from mangrove region of Sundarbans, India for enhanced crop productivity - Pallavi; Mishra, Rohit Kumar; Sahu, Pramod Kumar; Mishra, Vani; Jamal, Hafiza; Varma, Ajit; Tripathi, Swati (Frontiers in Plant Science, 2023)
Halotolerant plant growth promoting rhizobacteria (PGPR) are beneficial microorganisms utilized to mitigate the biotic and abiotic stresses in plants. The areas of Sundarban mangroves of West Bengal, India have been reported to be rich in halotolerant microflora, yet major area remains unexplored. The present study, therefore, aims to map down the region-specific native microbial community potent of salt tolerance, plant growth promoting (PGP) activity and antagonistic activity against fungal pathogens. Bacterial samples were isolated from the saline soil of the Sundarban mangroves. A total of 156 bacterial samples were isolated and 20 were screened for their salt tolerance potential. These isolates were characterised using morphological, biochemical, and molecular approaches. Based on 16s rRNA sequencing, they were classified into 4 different genera, including Arthrobacter sp. (01 isolate), Pseudomonas plecoglossicida (01 isolate), Kocuria rosea (01 isolate), and Bacillus (17 isolates). The halotolerant isolates which possessed plant growth promoting traits including phosphate, and zinc solubilization, indole acetic acid production, siderophore, and ammonia generation were selected. Further, the effect of two halotolerant isolates GN-5 and JR-12 which showed most prominent PGP activities was evaluated in pea plant under high salinity conditions. The isolates improved survival by promoting germination (36 to 43%) and root-shoot growth and weight of pea plant in comparison to non-inoculated control plants. In a subsequent dual culture confrontation experiment, both these halo-tolerant isolates showed antagonistic activities against the aggressive root rot disease-causing Macrophomina phaseolina (Tassi) Goid NAIMCC-F-02902. The identified isolates could be used as potential bioagents for saline soils, with potential antagonistic effect on root rot disease. However, further studies at the physiological and molecular level would help to delineate a detail mechanistic understanding of broad-spectrum defence against salinity and potential biotic pathogen.